Preparation and properties of nano ZnO toughed phenol–urea‐formaldehyde foam. Issue 6 (30th August 2020) - Wang, Zixuan; Zheng, Ting; Lu, Chunrui; Guo, Xiaona; Xiao, Haiying; Jia, Jin; Zhang, Dongxing
Abstract: Urea formaldehyde (UF) and phenol formaldehyde (PF) foam possess outstanding flame‐retardant properties, excellent insulation, and low thermal conductivity. These properties make them suitable for thermal insulation in buildings. However, the mechanical properties still need to be improved. In this study, orthogonal test was designed to optimize the level components of PF/UF composite foam first, then nano ZnO was added to the PF/UF composite foam to improve its toughness. The effects of nano ZnO on the morphology, apparent density, pulverization rate, thermal conductivity and thermal degradation property, flame retardancy, and mechanical properties of the ZnO/PF/UF nanocomposite foam were studied. The addition of nano ZnO improved the bending and compressive strength and decreased the pulverization rate of the composite foam significantly. The ZnO/PF/UF nanocomposite foam also presented better flame retardant properties than PF/UF composite foam. The largest oxygen index values of ZnO/PF/UF nanocomposite foam could reach 39.31%, while the thermal conductivity and the maximum rate of weight loss temperature were increased to 0.036 W/(m∙K) and 279°C, respectively. Moreover, ZnO/PF/UF nanocomposite foam showed low apparent density property (0.27 g/cm 3 ). Abstract : The low density, high strength and flame retardant ZnO/PF/UF nanocomposite foams were fabricated via in situ polymerization in this paper. The addition of nano ZnO particles could not only improve the mechanical properties of PF/UF composite foam, but can also enhance the flame retardant properties of the PF/UF composite foam. The obtained nanocomposite foams could be used as thermal insulation in buildings.